Radical Humanism and Management: the implications of humanism for business administration and studies - Aktouf, Omar; Holford, W. David (Organizações & Sociedade, 2014)
The dialectical nature of the current socio-economic process at work, namely, the endless pursuit of maximization of profits leading towards a truncated understanding of Man, which in turn leads towards the further quest for maximization of profits, and so on, appears to pose an endless impasse. Breaking this negative dialectic involves: 1) having managerial studies develop and adopt an understanding and theory of Man that embraces a “radical humanism”; and 2) adopting a conception of corporate governance that aims to serve Mankind in lieu of exploiting it. The radical humanism referred to in this paper considers the human being as a being of speech, of symbols, of senses, of society, of free-will, and not just simply as a resource at the service of the company and of maximization of profit. Embracing a radical humanism, as well as a governance that aims to serve Man rather than exploit him introduces a virtuous dialectic: the adoption of a fuller understanding and respect for Man and Nature leads to the production and subsequent sharing of profits, which in turn reinforces the respect and understanding of Man and Nature, leading to further profits (and subsequent sharing), and so on. Adopting a humanistic approach within business activities and interactions is of the utmost priority if society, and by extension, we as human beings both in the individual and collective sense, are to survive, flourish and emancipate ourselves. At first glance, mainstream management literature would appear to be showing encouraging ‘signs’ of enlightenment across the myriad of leitmotivs that are discerned across such words as “humanism”, “ethics”, “corporate governance”, “social responsibility for business”, and “environmental responsibility”. In fact, if there is a major point of convergence for the many streams of literature, it is the importance of the human person or personal attitudes and behaviors at work. No matter the trend or topic: whether it is about corporate ‘culturalism’ (Deal & Kennedy, 1982; Ouchi, 1981; Peters & Waterman, 1982; Schein 1985 and 1991) or motivation and the valorization of human resources (Peters and Austin, 1985; Waterman, 1987; Crozier, 1989; Archier and Serieyx, 1987); whether it is across total quality, the re-introduction of the meaning of work, ‘empowerment’ (Juran and Gryna, 1980; Michel, 1989; Serieyx, 1989; Peters and Austin, 1985; Mintzberg, 1989) or the realization of the workplace as an area of social interactions and sharing (Peters and Austin, 1985; Weitzman, 1984; Peters, 1987; DePree, 1989); or whether it is the various pre-occupations on ethics, ethico-spirituality or other management methods aiming towards cohesion, participation, initiative and creativity at all levels, what stands out most clearly is the insistent call from all quarters on putting the human element at the forefront. Yet let us not fool ourselves into thinking that these various streams reflect any significant attempt at creating business frameworks or management practices that embrace man’s emancipation as a finality onto itself, or “man as being the measure of all things”.